The technological value of the sugar beet = La valeur technique de la betterave sucriere = Der Technische wert der Zuckerrube : Proceedings of the XIth Session of the Commission Internationale Technique de Sucrerie, Frankfurt, 1960. (Elsevier Publishing Company, 1962)
The Technological Value of the Sugar Beet focuses on the physical properties of the beet with respect to storage, slicing, diffusion, and filtration rate, as well as the chemical composition of the juice which determines the ash, lime salts, nitrogenous constituents, and other nonsugars in factory process liquors. The selection first offers information on the characteristics of the technological value of the sugar beet, including morphological characters, chemical characteristics, effects of chemical beet characteristics on the characteristics of the thick juice, and multiple correlations. The.